Determinan pengungkapan corporate social responsibility pada perusahaan pertambangan di BEI - Rizky Windar Amelia; Anis Marjukah; Agung Nugroho Jati; Abidah Dwi Rahmi Satiti (Universitas Kristen Maranatha, 2024)
The disclosure of corporate social responsibility (CSR) by businesses, particularly those in the mining industry, is still not optimal. A program for striking a balance between financial gains and benefits to the economy, society, and environment is known as corporate social responsibility. The community requires information on CSR initiatives in order to satisfy its right to a sense of safety, security, and prosperity. A business focus shifts from internal responsibility to environmental and social issues as a result of corporate social responsibility. This study aims to analyze and examine the factors influence of company size, GCG, and DER on the disclosure of CSR in the mining company listed on the Indonesia Stock Exchange 2018-2022 period. This study uses regression analysis with quantitative methods. Purposive sampling was used to collect a total of 55 samples from 11 businesses for this study, so that the mining companies were obtained according to the criteria and had complete financial ratio data. Having collected the data, they were analyzed using multiple linear regression. Based on analysis, the results of this study show that the disclosure of corporate social responsibility is significantly influence by company size and DER, while the GCG have insignificant effect on the disclosure of CSR in mining company listed on Indonesia Stock Exchange 2018-2022 period. The finding of this study not only helps development of science, but also helps management of mining companies to comply with government policies and ensure that if policies are followed so that the company do not violate applicable regulations.